Breast Feeding Practices In Rural And Urban Communities In A Hilly District Of North India - Gupta Anmol K; Sood Rajesh K; Vatsayan Ajay; Dhadwal Dineshwar K; Ahluwalia Surendra K; Sharma Rajesh K (Wolters Kluwer Medknow Publications, 1997)
Research question: What are the breast feeding practices in urban and rural communities of a hilly district? Objectives: 1. To study breast feeding practices. 2. To find out the influence of motherâ€s education on these practices. Study Design: Cross-sectional Setting: Urban and Rural Participants: Mothers of under 3 years children Sample size: 994 subjects(489 from urban and 505 from rural areas) Study variables: Prelacteal feed, initiation of breast feeding, complimentary feed introduction, continued breast feeding, material literacy, urban and rural subjects. Statistical analysis: Proportions and chi-square test. Results: A high exclusive breast feeding rate was observed which was 0.74 in urban and 0.72 in rural children less than 4 months of age. Timely complementary feeding rate was 0.84 and 0.70 in urban and rural areas respectively. Continued breast feeding rates at 1 and 2 years were 0.44 to 0.65 and 0.15 to 0.36 in urban and rural areas respectively.